Lithic bacterial communities: ecological aspects focusing on Tintenstrich communities - Pittino, Francesca; Fink, Sabine; Oliveira, Juliana; Janssen, Elisabeth M.-L.; Scheidegger, Christoph (Frontiers in Microbiology, 2024)
Tintenstrich communities (TCs) mainly comprise Cyanobacteria developing on rock substrates and forming physical structures that are strictly connected to the rock itself. Endolithic and epilithic bacterial communities are important because they contribute to nutrient release within run-off waters flowing on the rock surface. Despite TCs being ubiquitous, little information about their ecology and main characteristics is available. In this study, we characterized the bacterial communities of rock surfaces of TCs in Switzerland through Illumina sequencing. We investigated their bacterial community composition on two substrate types (siliceous rocks [SRs] and carbonate rocks [CRs]) through multivariate models. Our results show that Cyanobacteria and Proteobacteria are the predominant phyla in this environment. Bacterial α-diversity was higher on CRs than on SRs, and the β-diversity of SRs varied with changes in rock surface structure. In this study, we provide novel insights into the bacterial community composition of TCs, their differences from other lithic communities, and the effects of the rock substrate and structure.